Corporate Bond Liquidity during the COVID-19 Crisis. (21st May 2021) - Kargar, Mahyar; Lester, Benjamin; Lindsay, David; Liu, Shuo; Weill, Pierre-Olivier; Zúñiga, Diego
Abstract: We study liquidity conditions in the corporate bond market during the COVID-19 pandemic. We document that the cost of trading immediately via risky-principal trades dramatically increased at the height of the sell-off, forcing customers to shift toward slower agency trades. Exploiting eligibility requirements, we show that the Federal Reserve's corporate credit facilities have had a positive effect on market liquidity. A structural estimation reveals that customers' willingness to pay for immediacy increased by about 200 bps per dollar of transaction, but quickly subsided after the Fed announced its interventions. Dealers' marginal cost also increased substantially but did not fully subside.